The effect of polyethyllene gyicol (Peg) on protein output of free range Alentejano pigs - Ferraz de Oliveira, M.I. (2008)
The effect of PEG treated or untreated acorns fed to Alentejano pigs, on the protein output of the animals were studied. The animals had access to two sown pasture fields based on Trifolium incarnatum and Lolium westerwoldicum. Four dietary treatments were tested with 5 pigs per treatment in a two by two factorial experimental design (factor 1: sown species; factor 2: acorn with or without PEG). Intake of acorns and protein faecal concentration were measured individually. Faecal output was estimated using an external faecal marker (dotriacontane, C32). Crude protein faecal concentration of animals fed acorns treated with PEG was significantly lower (P<0,05) then those fed untreated acorns, suggesting that the PEG may have increased the availability of dietary protein to the animals. However, the estimation of protein faecal output using the n-alkane C32 was not significantly affected by the PEG treatment, even though, for the animals in the Lolium westerwoldicum pasture, there was a decrease (P=0,063) in the total excretion of CP when acorns were treated with PEG.